Sifat Kimia Kayu Salam (Zyzigium Polyantha Wight)*) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT Laboratory Fac. of Forestry, GMU in 1991. The research objectives was to set up a data bank of salam wood for timber quality assessment. Wood samples was procurred from Karang Nongko village, Klaten. Wood meal of pa'ssing 45 and retained 60 mesh was prepared for chemical analyses. ASTM procedures was followed. Results showed that this salam wood contained low class up to moderate of extractives which dissolved in cold and hot water and alcohol-benzene mixture. The average of 3.09, 4.50 and 3.37% were detected for cold, hot and alcohol-benzene extractive content consecutively. The average of holo and alphacellulose content were 77.99 and 41.27%, while lignin and ash content were 33.38 and 0.82%.